'And I thought having a cancer diagnosis was hard': A descriptive phenomenological study of family caregiver experiences navigating the pre-hospital system during COVID-19. (February 2023) - Ma, Haixia; Zhao, Tuan; Wan, Chuchu; Liu, Fang; Christensen, Martin
Abstract: Purpose: Cancer patients usually need frequent hospitalization for diagnosis and treatment. However, the unprecedented outbreak of the Omicron wave in Shanghai pressured local communities and hospitals to enforce strict control measures. This qualitative study aimed to investigate cancer family caregivers' experiences of navigating the pre-hospital system during the lockdown in Shanghai. Method: This is a substudy of a larger study investigating the experience of 20 caregivers of hospitalized cancer patients during the lockdown in Shanghai. This study was based on findings from a subset of 14 semi-structured face-to-face interviews with cancer family caregivers. Inductive thematic analysis was used to analyze the data. Results: The outbreak of the epidemic and lockdown measures created additional challenges for caregivers, which extended beyond their daily concerns. Uncertainties of the situation, risks of infection, and income loss, along with the strict restrictions in their community and hospitals, added to their burden and compromised their abilities to seek help for their significant others. Yet, in an attempt to reduce undue concern and worry, caregivers were eventually allowed to accompany their family member to the hospital using reliable information, and telemedicine techniques based on an updated governmental policy governing access to care and support for cancer patients. Conclusions: The lockdown in Shanghai significantly affected cancer family caregivers' experience navigating the pre-hospital system. Policy support for cancer care, reliable information, and telemedicine techniques have been identified as essential facilitators of improved access to cancer care. Highlights: Cancer patients experienced difficulties in accessing timely cancer care during the COVID-19 pandemic. The outbreak of the epidemic and lockdown measures created additional challenges for cancer family caregivers. Despite the challenges, family caregivers made significant efforts to navigate the pre-hospitalisation processes.